Belajar Mandiri Melalui Pengembangan Diri Gaya Belajar yang Disukai (Studi Kasus pada Mahasiswa FKIP Bahasa Inggris Universitas Wiralodra Indramayu) - Nasir (Counselia, 2026)
Student learning success is determined by the achievement of learning objectives that include cognitive, affective, and psychomotor aspects, which are influenced by internal and external factors. One crucial element in the effectiveness of independent learning is choosing the right learning style. This study aims to analyze the learning style tendencies of third-semester students of the English Language Education Study Program, FKIP, Wiralodra University in 2025 and the self-development strategies they carry out. The research method used is a case study with a quantitative descriptive approach. The results of the study show variations in learning style preferences as follows: (1) Dominance of Visual learning styles (40.9%), where students find it easier to understand material through graphical representations such as mind maps, learning videos, and colored notes; (2) Visual-Auditorial learning styles (31.8%) which rely on a combination of visual objects with oral explanations and discussions; (3) Auditory learning styles (13.6%) which focus on listening through audio, podcasts, and reading aloud techniques; and (4) Visual-Kinesthetic learning styles (13.6%) which prioritize visualization accompanied by direct practice or simulation. Independent learning strategies implemented by students include creating infographics, visual summaries, group discussions, and practical experiments. The study's conclusions indicate that the majority of students tend to prefer visual and visual-auditory learning styles because they are considered more logical and realistic in supporting independent understanding of the material. This study recommends that lecturers plan learning processes that accommodate various learning styles to increase student engagement and independence in learning.